Thermostabilization mechanisms in thermophilic versus mesophilic three‐helix bundle proteins. Issue 3 (5th November 2021) - Nguyen, Catrina; Yearwood, Lauren M.; McCully, Michelle E.
Abstract: The engineered three‐helix bundle, UVF, is thermostabilized entropically due to heightened, native‐state dynamics. However, it is unclear whether this thermostabilization strategy is observed in natural proteins from thermophiles. We performed all‐atom, explicit solvent molecular dynamics simulations of two three‐helix bundles from thermophilic H. butylicus (2lvsN and 2lvsC) and compared their dynamics to a mesophilic three‐helix bundle, the Engrailed homeodomain (EnHD). Like UVF, 2lvsC had heightened native dynamics, which it maintained without unfolding at 100°C. Shortening and rigidification of loops in 2lvsN and 2lvsC and increased surface hydrogen bonds in 2lvsN were observed, as is common in thermophilic proteins. A buried disulfide and salt bridge in 2lvsN and 2lvsC, respectively, provided some stabilization, and addition of a homologous disulfide bond in EnHD slowed unfolding. The transferability and commonality of stabilization strategies among members of the three‐helix bundle fold suggest that these strategies may be general and deployable in designing thermostable proteins. Abstract : The ability to engineer proteins that can withstand extreme temperatures broadens the potential applications for protein design. Here, we compared the dynamics of a naturally thermostable protein to its mesophilic homologue. We observed well‐established thermostabilization strategies such as rigidification of loops and inclusion of a buried disulfide bond and salt bridge, as well as a potential new avenue for protein design, thermostabilization via dynamics.